Correlation of Dissolved Oxygen and Nitrate in Aquaculture Pond Integrated Sensor System - C. M. Zhen, M.F. Mohd Amin, S. Onsanit, M. S. M. Rasat, N. H. Abdullah, T.C. Ling, K.N.S.W.S. Wong, N. Adnan, N.J. Ramli (International Journal of Advanced Science and Technology, 2020)
The production of aquaculture has a great potential and high demand in the Asia country. The production of aquaculture is increased with a good water quality in the fishpond. A good water quality must be maintained and monitored by using the smart water monitoring system which is a real-time measurement to assess and monitor the status of water quality regularly, to obtain the real-time data at anytime and anywhere. This system gives early short warning notification through phone message. The purpose of this study is to evaluate and estimate the relationship between nitrate and dissolved oxygen by using the correlation and regression analyses in Statistic Package for Social Science (SPSS) software. The data are collected by the sensor and sent to the computer for assessing and analyzing the data. In the result, the smart water monitoring system is verified with the portable water quality equipment due to both readings are approximately similar with each other. Overall, the value of the parameters was in an acceptable range and the water quality in this pond was considered good.  The result of correlation analysis showed that there is a strong negative correlation and significant relationship between nitrate and dissolved oxygen with p-value is lower than 0.01 and 0.05. In the overall result of regression analysis, 99.3% of the behavior of nitrate can be explained and predicted by dissolved oxygen. Most of the assumptions of regression analysis are met which is considered as the regression model is fitted with the data. The sensor system also shows a good performance in capturing quality data throughout this studyKeywords: sensor, data analysis, aquaculture, water quality.